Fatty acids can inhibit Staphylococcus aureus SaeS activity at the membrane independent of alterations in respiration. Issue 5 (30th October 2021) - DeMars, Zachary R.; Krute, Christina N.; Ridder, Miranda J.; Gilchrist, Aubrey K.; Menjivar, Cindy; Bose, Jeffrey L.
Abstract: In Staphylococcus aureus, the two‐component system SaeRS is responsible for regulating various virulence factors essential for the success of this pathogen. SaeRS can be stimulated by neutrophil‐derived products but has also recently been shown to be inactivated by the presence of free fatty acids. A mechanism for how fatty acids negatively impacts SaeRS has not been described. We found that unsaturated fatty acids, as well as fatty acids not commonly found in Staphylococcal membranes, prevent the activation of SaeRS at a lower concentration than their saturated counterparts. These fatty acids can negatively impact SaeRS without altering the respiratory capacity of the bacterium. To uncover a potential mechanism for how fatty acids impact SaeRS function/activity, we utilized a naturally occurring point mutation found in S. aureus as well as chimeric SaeS proteins. Using these tools, we identified that the native transmembrane domains of SaeS dictate the transcriptional response to fatty acids in S. aureus . Our data support a model where free fatty acids alter the activity of the two‐component system SaeRS directly through the sensor kinase SaeS and is dependent on the transmembrane domains of the protein. Abstract : Fatty acids can inhibit SaeS activity with unsaturated fatty acids generally being stronger inhibitors than saturated fatty acids. This suppression occurs at the membrane and is independent of SaeP, SaeQ, and changes in respiratory activity, but requires the native SaeS transmembrane domains. Created with BioRender.com .